CONTEXTUAL TEACHING LEARNING TO IMPROVE STUDENTS' CRITICAL THINKING SKILL AND CONCEPT COMPREHENSION IN CHANGES OF MATTER TOPIC FOR JUNIOR HIGH SCHOOL - Pramana, Afif Naofal (2014)
Nowadays, almost all science education always given only transfer of knowledge from teacher to students with remembering or formulas, only to pass the examination or answer the question, but usually students cannot describe what they have learned with the environment. Implementation of contextual teaching to improve students' critical thinking skill in changes of matter concept has been conducted. The study adopted a weak-experimental method using "one group pretest-posttest design". The purpose of this study is to describe the implementation of contextual teaching in improving the students' critical thinking skill. Population in this research are 15 students in grade 7 of junior high school students at one of International School in Bandung. The sample was taken by using availability sampling method. The research data was gained through item tests that were given in pre-test and post-test. The Questionnaire was also applied to get information on students' responses for the contextual teaching. The result indicates an increasing in students' critical thinking and concept comprehension. The relationship is when the improvement of critical thinking skill influence to improvement of concept comprehensive. Students are able to identify the problems that exist in the environment issues and determine the solution of the problems, also applying the solution. Besides, the students' achievement has been passed the minimum criteria of completeness.